Single‐Nucleotide Polymorphism C3435T in the ABCB1 Gene is Associated with Opioid Consumption in Postoperative Pain. Issue 12 (19th August 2013) - Candiotti, Keith; Yang, Zhe; Xue, Lihua; Zhang, Yanping; Rodriguez, Yiliam; Wang, Liyong; Hao, Shuangling; Gitlin, Melvin
Abstract Background ABCB1 is a major determinant of opioid bioavailability; however, no previous studies have provided positive evidence of an association between single‐nucleotide polymorphisms (SNPs) of ABCB1 and opioid usage in acute pain management. The aim of this study was to test the association between the functional SNP C3435T in ABCB1 and opioid consumption in postoperative pain in patients undergoing a nephrectomy. Additionally, we explored the association between C3435T and opioid side effect. Methods C3435T was genotyped in 152 patients undergoing a nephrectomy. Opioid consumption and pain scores were evaluated as well. The effect of genotype on opioid consumption was modeled using a general linear mixed model. Result Based on a mixed linear model, the ABCB1 three genotypes showed a statistically significant effect on opioid consumption (F = 4.20, P = 0.017). There was a statistically significant difference in opioid consumption among the ABCB1 three genotypes in the 0–6 hours (P = 0.031, 95% confidence interval [CI] CC 14.7–24.8 mg and TT 5.2–14.6 mg) and 6–12 hours (P = 0.009, 95% CI CC 5.6–13.8 mg and TT 1.2 mg–5.1 mg) postoperative period. There were no significant statistical differences in opioid consumption among the ABCB1 three genotypes in the 12–24 hours (P = 0.302) and 24–48 hours (P = 0.763) postoperative period. The TT genotype had significantly lower levels of cumulative opioid consumption compared with the CC genotype in first 24 hours after surgery (P = 0.029). No statistically significant differences among the three genotype groups were noted for postoperative pain scores or emesis medication use in the first 24 hours after surgery. Conclusion Our results demonstrate an association between the ABCB1 polymorphism (C3435T) and interindividual variations in opioid consumption in the acute postoperative period after nephrectomy. The ABCB1 polymorphism may serve as an important factor to guide acute pain therapy in postoperative patients.